2019
DOI: 10.1080/14786419.2019.1587426
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositions and antimicrobial activities of the essential oil from Pterocarya stenoptera C. DC

Abstract: The present study investigated the chemical compositions and antimicrobial activities of essential oil from Pterocarya stenoptera. The essential oil obtained by hydrodistillation from the dried leaves of P. stenoptera was analysed by GC-MS and 39 constituents accounting for the total 90.44 % of the oil were identified.The main constituents were δ-cadinene (24.83%), caryophyllene oxide (9.10%), α-cadinol (7.48%) and β-elemene (6.24%). The antimicrobial activity of the oil was evaluated by disc diffusion and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…To further understand the chemical constituents of the PSBE, the main compounds in the PSBE were analyzed via UPLC/MS. As shown in Table 1 and Fig Previous studies have identified 39 compounds from the essential oil of P. stenoptera by researchers (Yin et al 2020). However, there is still little research on the non-volatile chemical composition of P. stenoptera.…”
Section: Uplc-ms/ms Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…To further understand the chemical constituents of the PSBE, the main compounds in the PSBE were analyzed via UPLC/MS. As shown in Table 1 and Fig Previous studies have identified 39 compounds from the essential oil of P. stenoptera by researchers (Yin et al 2020). However, there is still little research on the non-volatile chemical composition of P. stenoptera.…”
Section: Uplc-ms/ms Analysismentioning
confidence: 97%
“…In recent years, the biological activities of the extracts from P. stenoptera have been preliminarily studied. It has been reported that the essential oil of P. stenoptera has a strong inhibitory effect on Staphylococcus aureus, Bacillus subtilis, Salmonella typhimurium, Vibrio parahaemolyticus, and Candida albicans (Yin et al 2020). In addition, studies show that P. stenoptera bark extract has excellent antiviral effects (Cheng et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the Pterocarya spp. has been used to treat bacterial and fungal skin diseases and also utilized as a diaphoretic, antidiarrheal, and anesthetic agent 7,8 . A recent study showed that the ethyl acetate layer and six pure compounds obtained from the ethanol extract of Pterocarya hupehensis have various bioactivities such as antioxidant, anti‐inflammatory and antimicrobial, and in terms of antimicrobial activity, the minimum inhibitory concentration (MIC) values of the six compounds against Staphylococcus aureus , Escherichia coli , Pseudomonas aeruginosa , and Candida albicans ranged from 0.5 to 2 mg mL −1 9 .…”
Section: Introductionmentioning
confidence: 99%
“…has been used to treat bacterial and fungal skin diseases and also utilized as a diaphoretic, antidiarrheal, and anesthetic agent. 7,8 A recent study showed that the ethyl acetate layer and six pure compounds obtained from the ethanol extract of Pterocarya hupehensis have various bioactivities such as antioxidant, antiinflammatory and antimicrobial, and in terms of antimicrobial activity, the minimum inhibitory concentration (MIC) values of the six compounds against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans ranged from 0.5 to 2 mg mL −1 . 9 In addition, Yin et al reported that the essential oil from Pterocarya stenoptera, consisting of 39 constituents, exhibits broad-spectrum antibacterial activities against Staphylococcus aureus, Salmonella typhimurium, and Bacillus subtilis, suggesting that essential oil of Pterocarya stenoptera can be a potential source of natural antimicrobials in the food preservation and pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation